Effects of vitamin K supplementation on bone mineral density at different sites and bone metabolism in the middle-aged and elderly population: a meta-analysis and systematic review of randomized controlled trials - Chenqi Xie; Jianbao Gong; Chenglong Zheng; Junwei Zhang; Jie Gao; Chunyan Tian; Xiaofei Guo; Shiyou Dai; Tianlin Gao (Bone & Joint Research)
Aims: This meta-analysis and systematic review aimed to comprehensively investigate the effects of vitamin K supplementation on bone mineral density (BMD) at various sites and bone metabolism in middle-aged and older adults. Methods: The databases of PubMed, Web of Science, and Cochrane Library were thoroughly searched from inception to July 2023. Results: The results revealed that vitamin K supplementation increased BMD at the lumbar spine (p = 0.035). Moreover, the pooled effects demonstrated a notable increase in carboxylated osteocalcin (cOC) (p = 0.004), a decrease in uncarboxylated osteocalcin (ucOC) (p < 0.001), and no significant effect on total osteocalcin (tOC) (p = 0.076). Accordingly, the ratio of cOC to ucOC (p = 0.002) significantly increased, while the ratio of ucOC to tOC decreased (p = 0.043). However, there was no significant effect of vitamin K supplementation on other bone metabolism markers, such as cross-linked telopeptide of type 1 collagen (NTx), bone alkaline phosphatase (BAP), and procollagen I N-terminal propeptide (PINP). Subgroup analysis revealed that vitamin K notably enhanced bone health in females by increasing lumbar spine BMD (p = 0.028) and decreasing ucOC (p < 0.001). Vitamin K, especially vitamin K2, exhibited effects on maintaining or increasing lumbar spine BMD, and influencing the balance of cOC and ucOC. Conclusion: This review suggests that the beneficial effects of vitamin K supplementation on bone health primarily involve enhancing the carboxylation of OC rather than altering the total amount of OC. Cite this article: Bone Joint Res 2024;13(12):750–763.